On the taxonomy and host plants of North European species of Eupontania (Hymenoptera: Tenthredinidae: Nematinae). - Vikberg, Veli; Zinovjev, Alexej Glebovitsch (Contributions to Entomology = Beiträge zur Entomologie, 2006)
In Europe Eupontania is comprised of the vesicator-, viminalis-, aquilonis-, and crassipes-groups. From Northern Europe 13 species of the Eupontania viminalis group are recorded. Eupontania brevicornis (Förster, 1854), sp. rev. and comb. n. (= Nematus congruens Förster, 1854, syn. n., Pontania carpentieri Konow, 1907, syn. n., Pontania pedunculi auct., nec Hartig) inducing galls on the leaves of Salix cinerea L. is recorded from Finland and compared with closely related E. arcticornis (Konow, 1904) forming galls on Salix phylicifolia L. The taxonomy and host plants of Eupontania pedunculi (Hartig, 1837) (= Nematus bellus Zaddach, 1876; Pontania gallarum auct., nec Hartig), and E. gallarum (Hartig, 1837) (= N. aestivus Thomson, 1863, syn. n.; Pontania varia Kopelke, 1991, syn. n.; Pontania norvegica Kopelke, 1991, syn. n.) are briefly discussed. E. pedunculi is treated as a species inducing galls on several species of the section Vetrix other than S. cinerea: Salix aurita L., S. caprea L., S. starkeana ssp. starkeana Willd. and ssp. cinerascens (Wahlenb.) Hultén (= S. bebbiana Sarg.). E. myrtilloidica (Kopelke, 1991) from galls on S. myrtilloides L. is recorded from Finland but its taxonomic status remains uncertain. The host plant of E. gallarum is Salix myrsinifolia Salisb. including ssp. borealis (Fr.) Hyl. Lectotypes are designated for Pontania arcticornis, P. phylicifoliae Forsius, 1920, P. viminalis var. hepatimaculae Malaise, 1920, Nematus brevicornis, P. samolad Malaise, 1920 (host plant S. lapponum L.), and P. pustulator Forsius, 1923. A neotype for Nematus gallarum is designated from Sweden, Uppland. E. acutifoliae baltica ssp. n. is described from Lithuania, Estonia, Russia, and Finland, and E. collactanea rosmarinifoliae ssp. n. is described from Finland and Russia. The list of host plants for 20 described species of Eupontania from Northern Europe is given. E. pustulator recorded for the first time on Salix pulchra Chamisso from the Polar Urals.KeywordsTenthredinidae, Pontania, Eupontania, sawflies, hostplants, Salix.Nomenclatural Actsarcticornis (Konow, 1904) (Eupontania), Lectotype described as Pontania arcticornisbrevicornis (Förster, 1854) (Eupontania), Lectotype; spec. revocata described as Nematus brevicornisgallarum (Hartig, 1837) (Eupontania), Neotype described as Nematus gallarumpustulator (Forsius, 1923) (Eupontania), Lectotype described as Pontania pustulatorsamolad (Malaise, 1920) (Eupontania), Lectotype described as Pontania samoladbaltica Vikberg & Sinovjev, 2006 (Eupontania acutifoliae), sspec. n.rosmarinifoliae Vikberg & Sinovjev, 2006 (Eupontania collactanea), sspec. n.congruens Förster, 1854 (Nematus), syn. n. of Eupontania brevicornis (Förster, 1854)carpentieri Konow, 1907 (Pontania), syn. n. of Eupontania brevicornis (Förster, 1854)phylicifoliae Forsius, 1920 (Pontania), Lectotype now a syn. of Eupontania arcticornis (Konow, 1904); Lectotype design. by Kopelke (1991) was invalidhepatimaculae Malaise, 1920 (Pontania vinimalis var.), Lectotype now a synonym of Eupontania arcticornis (Konow, 1904)